Phosphorus Alleviates Cadmium Damage by Reducing Cadmium Accumulation and Enhancing Antioxidant Enzymes at the Vegetative Phase in Soybean - Sen Jia; Xiang Zhao; Junxia Huang; Xingdong Yao; Futi Xie (Agronomy)
Cadmium (Cd) is a toxic, non-essential heavy metal, with significant stress to plants such as soybean (Glycine max). High Cd concentration in the soil inhibits various stages of soybean growth, including seed germination, vegetative growth, and the reproduction stage. Phosphate, a vital macronutrient, has been shown to alleviate Cd-induced stress; however, the molecular mechanisms remain poorly understood. This study aimed to explore the interactive effects of Cd and phosphate on soybeans at the physiological, transcriptomic, and metabolic levels using a multi-omics approach. Experiments were conducted where soybean plants were treated with different concentrations of Cd and phosphate. The results indicated that Cd stress significantly reduced plant height, photosynthetic rate, and transpiration rate, while phosphorus application mitigated these effects, reducing Cd absorption in both roots and shoots. Furthermore, antioxidant enzyme activities (superoxide dismutase, catalase, and peroxidase) were significantly enhanced by phosphate under Cd stress, which scavenged reactive oxygen species (ROS) generated by cadmium, thereby protecting cells from oxidative stress damage. Transcriptome and metabolome analyses revealed substantial changes in gene expression and metabolite profiles in response to Cd and phosphate treatments. Notably, phosphorus treatment induced the up-regulation of genes involved in stress response, root development, and metal transport, while altering metabolic pathways related to phenolic acids, flavonoids, and lipids. This research provided new insights into the molecular mechanism by which phosphorus enhanced the activity of antioxidant enzymes, thereby improving the plant’s antioxidant defense capacity and reducing the toxic effects of cadmium in soybeans, offering potential strategies for enhancing crop resilience against heavy metal contamination.